In situ photothermal catalytic cell for X-ray absorption fine structure spectroscopy measurement - Bingbao Mei; Di Shen; Yao Wei; Jingyuan Ma; Fanfei Sun (Materials Today Catalysis)
The burgeoning field of photothermal catalysis has garnered increasing interest due to the synergistic effects of light and thermal activation. Understanding the intrinsic reaction dynamics and structural evolution during the photothermal catalytic process is crucial for the design of effective photothermal devices and catalysts, as well as for optimizing photothermal performance. In situ X-ray absorption fine structure (XAFS) spectroscopy under operational conditions provides a powerful tool for revealing deep insights into atomic and electronic structures. In this study, we designed and constructed a multifunctional in situ photothermal catalytic cell for XAFS measurement, incorporating gas flow, optical sensing, temperature control, and monitoring. We detail the systematic design of the cell, facilitating the further development of portable and effective devices. To validate the cell’s performance, we used commercial WO3 powder as a reference and obtained high-quality XAFS spectra under the influence of light and heat; we also explored the enhanced charge separation efficiency and the consequent improvement in reaction kinetics due to light irradiation. This study underscores the critical role of in situ cells in operational settings and offers a novel perspective on the mechanisms underlying photothermal reactions.